Pengaruh Takaran dan Frekuensi Aplikasi PGPR terhadap Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa L.). - Yohanes F. Naihati; Roberto I. C. O. Taolin; Aloysius Rusae (Savana Cendana, 2018)
The aim of this research is to know and prove the influence of dosage and frequency of PGPR application on growth and yield of lettuce, and also to know the exact dosage and frequency of PGPR application to get the best growth and yield of lettuce. The design used was factorial randomized block design with three replications. The first factor is a dose of PGPR consisting of three levels ie 25 g, 50 g, and 75 g. The second factor is the application frequency consisting of three levels ie without watering (control), one-time watering, and two times watering. The results showed an interaction between dose and frequency of application of PGPR occur in all parameters of growth and yield of lettuce ie plant height, leaf number, leaf area, fresh weight and dry weight of the plant without roots, root weight both fresh and dried, fresh weight and dry weight every plant, fresh weight and dry weight of plant every plot and harvest index. The application of PGPR twice with a dose of 25 g gives the best growth and yield of lettuce.